DIRECTIONS FOR IMPROVING THE CREDIT POLICY OF COMMERCIAL BANKS IN FINANCIAL SUPPORT OF THE ACTIVITIES OF ENTREPRENEURIAL SUBJECTS (Multidisciplinary Journal of Science and Technology, 2026)
The article analyzes the directions of improving the credit policy of commercial banks in financial support of small businesses. The role of small businesses in economic development and the difficulties in their financing are considered. Based on the results of the study, it was shown that it is possible to ensure the sustainable development of small businesses by making the credit policy of commercial banks effective. The article analyzes the existing credit mechanisms, interest rates, terms, and guarantees, and makes proposals for increasing financial support through the introduction of simplified credit conditions, special financial instruments, and digital platforms. The results of the study are of practical importance for commercial banks and government agencies in developing a strategy for developing small businesses.